1984
DOI: 10.3750/aip1984.14.1-2.08
|View full text |Cite
|
Sign up to set email alerts
|

Effect of physiological factors, stress, and disease on hematological parameters of carp, with a particular reference to leukocyte pattern. II. Hematological results of stress in carp

Abstract: Effects of three stress-producing factors: capture, trans portation, and starving on hematological parameters of carp blood were studied. Oxygen deficiency and crowding of fishes occurring on capture and transportation as well as a 21-week starving were found to considerably affect the hematological parameters examined, the effect being confirmed by statistical tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 4 publications
2
9
0
1
Order By: Relevance
“…Rehulka and Adamec (2004) reported higher RBC and Hb in O. mykiss from cage culture compared to the fish reared in flow-through tanks. An increase in RBC under transportation stress was observed in C. carpio (Sopińska 1984) and in Sparus aurata under crowding stress (Montero et al 1999), while a decrease was reported in Colossoma macropomum subjected to capture and handling (Tavares-Dias et al 2001) and in S. aurata under simulated mild management stress (Pages et al 1995). Positive relationship between RBC in Paralichthys dentatus and dietary protein level was observed by Daniels and Gallagher (2000).…”
Section: Erythrocytesmentioning
confidence: 84%
“…Rehulka and Adamec (2004) reported higher RBC and Hb in O. mykiss from cage culture compared to the fish reared in flow-through tanks. An increase in RBC under transportation stress was observed in C. carpio (Sopińska 1984) and in Sparus aurata under crowding stress (Montero et al 1999), while a decrease was reported in Colossoma macropomum subjected to capture and handling (Tavares-Dias et al 2001) and in S. aurata under simulated mild management stress (Pages et al 1995). Positive relationship between RBC in Paralichthys dentatus and dietary protein level was observed by Daniels and Gallagher (2000).…”
Section: Erythrocytesmentioning
confidence: 84%
“…No significant change occurred in slender seahorses transported with EO of L. alba, indicating that this EO is beneficial to reduce stress. A reduction in the concentration of lymphocytes and an increase in the number of neutrophils was also observed in the common carp, Cyprinus carpio, and the channel catfish, Ictalurus punctatus, after being subjected to the stress of capture or transport (Sopinska, 1984;Ellsaesser & Clem, 1986), as well as in Nile tilapia following the stress of capture (Martins et al, 2004), the European eel, Anguilla anguilla, under the stress of handling (Johansson-Sjöbeck et al, 1978) and the common dab, Limanda limanda, after being subjected to acute stress (Pulsford et al, 1994). An increase in the number of leukocytes was found in tambaqui (Tavares-Dias et al, 2001) and in the hybrid tambacu C. macropomum x Piaractus mesopotamicus (Martins et al, 2002) after being subjected to handling.…”
Section: Transportmentioning
confidence: 96%
“…considered an ideal condition for transporting fish because fish sedated at this level exhibit reduced activity but are able to maintain partial equilibrium, swimming capacity, and avoid physical damage resulting from collision with plastic bags (Cooke et al, 2004). Stress can increase blood glucose levels (Biron & Benfey, 1994;Wendelaar-Bonga, 1997;Barcellos et al, 2003) and affect leukocyte levels (Sopinska, 1984;Dick & Dixon, 1985, Ellsaesser & Clem, 1986Pickering & Pottinger, 1987). The blood glucose level of the control slender seahorses increased after transport, which is in agreement with previous findings in Chinook salmon, Oncorhynchus tshawytscha (Barton et al, 1986), coho salmon, Oncorhynchus kisutch (Vijayan & Leatherland, 1989), brook trout, Salvelinus fontinalis (Biron & Benfey, 1994) and pirarucu, Arapaima gigas (Brandão et al, 2006), following transportation.…”
Section: Transportmentioning
confidence: 99%
“…On the basis of these results, the anemia is categorized as the hypochromic macrocytic type which was observed in haemopoietic disorders [36,46] and was not found in viral diseases [35,41,48]. Macrocytic hypochromic anemia was seen in long term starved common carp Cyprinus carpio (L.) [44] and it was caused by vitamin B12 deficiency [45].…”
Section: Discussionmentioning
confidence: 99%